Rapid serum agglutination and agar gel immunodiffusion tests associated to clinical signs in rams experimentally infected with Brucella ovis - Nozaki,Cristiane Nakada (2011)
The purpose of this study was to evaluate the agar gel immunodiffusion and the rapid serum agglutination tests associated to clinical signs in rams experimentally infected with Brucella ovis. The serological profile during the 12 months of infection showed a large fluctuation of antibodies that favors the failure in the diagnostic. The evaluation of tests after the experimental infection allowed to suggest that none of the tests were able to detect the infection throughout the period of study. The study reinforces the importance of considering the clinical signs to support the diagnosis of Brucella ovis infection in rams.